(untitled) (Research, Society and Development, 2022)
The present article is about the result of the Health Education action with the hospital care team on the management of feeding the elderly patient in Palliative Care. The objective was to report the experience of a Health Education group as a tool for action regarding the aspects of feeding the elderly in Palliative Care. This is a descriptive, exploratory, qualitative study, of experience report type, which occurred between the months of May and July 2020, in a medium-sized hospital in Fortaleza-CE, which received patients in chronic-critical and Palliative Care, from a supplementary health plan. Five meetings were held with the team, every other week. The narratives present in this excerpt were built from the results of the promotion of an educative and support semi-structured group with the assistance team of the referred hospital, with the intent of opening space for the care of the elderly patient in the process of feeding in Palliative Care and the collective construction of knowledge related to Palliative Care in Gerontology and the contribution of Speech Therapy in this process. From the activities developed in the group dynamics, it was perceived that the assistance strategies and Health Education, when carried out in a clear and objective way, propitiate the development of autonomy in the care and promotion of health. These are very relevant work tools, since they allow us to identify problems and seek solutions in a simple and dynamic way.